2010
DOI: 10.1074/jbc.m110.166892
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Selection of Novel Fully Human Monoclonal Antibodies That Neutralize Dickkopf-1 (DKK1) Inhibitory Function in Vitro and Increase Bone Mass in Vivo

Abstract: Wnt/LRP5 signaling is a central regulatory component of bone formative and resorptive activities, and the pathway inhibitor DKK1 is a suppressor of bone formation and bone mass accrual in mice. In addition, augmented DKK1 levels are associated with high bone turnover in diverse low bone mass states in rodent models and disease etiologies in human. However, examination of the precise role of DKK1 in the normal skeleton and in higher species requires the development of refined DKK1-specific pharmacological tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…It is noteworthy that multiple studies provided proof of concept that Dkk1 targeting by immunotherapy can be used efficiently in both protective and therapeutic manners against cancer. [42][43][44][45][46][47] Sato et al 46 found that anti-Dkk1 treatment was able to induce apoptosis of A549 lung cancer cells (which express high levels of Dkk1) by an unknown mechanism, which we believe could be the one we describe here. Furthermore, tumors formed in nude mice following A549 cells injection were significantly smaller in animals treated with anti-Dkk1 compared with controls, demonstrating that Dkk1 targeting by antibodies can efficiently inhibit tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 54%
“…It is noteworthy that multiple studies provided proof of concept that Dkk1 targeting by immunotherapy can be used efficiently in both protective and therapeutic manners against cancer. [42][43][44][45][46][47] Sato et al 46 found that anti-Dkk1 treatment was able to induce apoptosis of A549 lung cancer cells (which express high levels of Dkk1) by an unknown mechanism, which we believe could be the one we describe here. Furthermore, tumors formed in nude mice following A549 cells injection were significantly smaller in animals treated with anti-Dkk1 compared with controls, demonstrating that Dkk1 targeting by antibodies can efficiently inhibit tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 54%
“…25 Interestingly, however, Koch et al 26 found that wounding of epithelial monolayers returned the leading edge cells to a nonquiescent state with activated β-catenin signal but subsequent induction and secretion of Dkk-1. Given that the Wnt signaling cascade with its antagonist Dkk-1 has been proposed to have crucial roles for maintaining homeostasis of a variety of tissues including the skin, 27 and that the physiologic Dkk-1 level is of vital importance to maintaining its biological functions, 28 we speculate that curcumin could precisely control the Dkk-1 level in a temporospatial manner to regulate the downstream Wnt signaling pathway, as Dkk-1 has been shown to participate in a negative feedback loop in Wnt signaling as well. 29 However, more studies are required to fully elucidate its less well-understood role in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that these antibodies induce bone formation, reduce bone resorption, and thereby lead to an increase in bone volume in rodent and monkey models (171,172,177). Thus, anti-DKK may have a potential as treatment of osteoporosis.…”
Section: The Wnt/lrp5 Systemmentioning
confidence: 99%
“…As the Wnt ligands, as well as the downstream signaling molecules GSK3b and b-catenin, are rather ubiquitous and have been implicated in cancer progression, these are less attractive targets despite their obvious anabolic potential (169,170). On the other hand, the identification of the soluble inhibitors of Wnt signaling, such as sclerostin, DKK1-4, WIF, and sFRPs, identified a series of interesting targets for antibody and small-molecule inhibitor therapy (169), and especially sclerostin that appears rather bone specific and DKK1 have been explored extensively (171,172,173,174).…”
Section: The Wnt/lrp5 Systemmentioning
confidence: 99%